IgG4 related lung disease- a rare and novel mimic of malignancy and infections-a case series of three patients with a brief review of updated literature. (2021) - Nasrullah, Adeel; Javed, Anam; Alvi, Zara; Raja, Atif; Ashraf, Obaid; Malik, Khalid; Balaan, Marvin
Abstract: IgG4-related lung disease is an extremely rare and novel entity which is still poorly understood. We reviewed the 16 patients diagnosed with IgG4-related disease from October 2014 through December 2019 at our institution. The three cases that showed pulmonary involvement are included in this series. Of these, two patients had cavitary lung disease and developed aspergilloma and chronic cavitating aspergillosis after a prolonged course of steroid therapy, and one had isolated pulmonary nodule and ground glass opacity. We reviewed the updated literature and briefly described disease epidemiology, clinical characteristics, diagnostic approaches, and management strategies for IgG4-related lung disease.